3D Virtual Tour Rumah Gadang Istana Pagaruyuang Menggunakan Unreal Engine 4 Berbasis Desktop - Sean Rayhan; Hidra Amnur; Taufik Gusman (JITSI : Jurnal Ilmiah Teknologi Sistem Informasi, 2021)
3D Virtual Tour of Rumah Gadang Istana Pagaruyung is a desktop-based virtual tour application that aims to educate and make it easier for the public to get to know the Rumah Gadang Istana Pagaruyung, besides that users can also explore, enjoy the beauty of architecture and get useful information in certain parts interactively everywhere. while within the scope of the Pagaruyung Palace Gadang Palace. This application was built using the Unreal Engine 4 game engine and several supporting software such as Blender, Materialize, etc. The research method is qualitative research where strategic use is Design and Creation. This research uses observational data collection methods through existing media on the internet. The information presented is limited to general knowledge. Testing will be carried out using a PC or Laptop. Applications can run on desktops that have at least 1GB of VRAM memory, 2GB of total VGA memory, 2GB of RAM, and at least an Intel Core Duo processor